Pengaruh Pemanfaatan Biourine terhadap Tanaman Sayuran Sawi di Desa Parungseah Kecamatan Sukabumi Kabupaten Sukabumi: The Effect of Biourine Utilization on Mustard Cultivation in Parungseah Village Sukabumi District Sukabumi Regency - Ayu Shelvia; Reni Suryanti; Maya Purwanti (Politeknik Pertanian Bogor, 2022)
The amount of sheep urine waste and the need for environmentally friendly vegetables are increasing, however most farmers do not know the benefits of urine waste due to the lack of knowledge. This study aimed to determine the recommended dose of bio urine on the growth of mustard plants. The research was conducted in Parungseah Village, Sukabumi District, Sukabumi Regency. The research design consisted of 3 treatments, namely 1) P0 dose without bio urine, 2) P2 dose with 200 ml of bio urine and 3) 300 ml of bio urine. Data analysis using Anova test and followed by Duncan test if there is an effect. The results of the analysis stated that P2 or treatment with a dose of 300 ml of bio urine was the highest average which had a significant effect on plant height, number of leaves, leaf width, and harvest weight (P<0.05) of mustard greens. Research shows that the use of sheep urine waste as liquid organic fertilizer with the dose 200 ml can increase the productivity of mustard plants.